Preverjanje uporabnosti modela SiWaWa za simuliranje razvoja čistih bukovih in smrekovih enomernih sestojev v Sloveniji - Klopčič, Matija (Gozdarski vestnik, 2021)
Forest development models predict development of trees and forest stands according to tree, stand, site, and forest management factors. Due to complex nature of forest ecosystems and long production cycles, forest development modelling is an important feature of forest management. Stand models have been identified as suitable for decision support in forest management, an example of such a model is the Swiss model SiWaWa, which was tested in Slovenian forests in the present study. Forest development simulations for 10-y periods were performed on four samples of 50 permanent sample plots in unmanaged and managed pure beech and pure spruce stands. Afterwards, we compared the actual and modelled values of stand basal area G, number of trees N, and mean squared diameter Dg. Predicting the development of pure beech forests was fairly accurate, the root mean square error RMSE for G was 2,35 m2 /ha for unmanaged, and 3,42 m2 /ha and 4,35 m2 /ha for managed stands considering only harvesting or entire mortality, respectively. We cannot claim the same for the development of pure spruce stands. Measures of accuracy were significantly worse, the RMSE was 8,94 m2 /ha for unmanaged stands, and 6,13 m2 /ha and 6,11 m2 /ha for managed stands considering only harvesting or entire mortality, respectively. The SiWaWa model, parameterized for Swiss forests, seems to be applicable for simulating the development of pure beech forests without or with simulated fellings, but the model does not yet provide reliable simulations for pure spruce stands
Keywords: European beech; forest development model; forest development simulations; forest inventory; forest stand; gozdna inventura; gozdni sestoj; mean quadratic diameter; model razvoja gozdov; Norway spruce; number of trees; sestojna temeljnica; simulacije razvoja gozdov; srednje temeljnični premer; stand basal area; število dreves